28 Development of a systematic approach to reduce the likelihood of patient harm associated with anticoagulant therapy. (2nd February 2018) - Jedeikin, R; Rutt, K; Trujillo, S; Preston, T; Olson, S
Abstract : Purpose: Coumadin identified by Institute for Safe Medication Practice as high–risk medication with narrow therapeutic window and high risk of life threatening adverse effects Anticoagulants identified as one of the top five drug types associated with patient safety incidents Maintaining INR in recommended therapeutic ranges reducing the incidence of adverse effects Improve INR–TTR(time in therapeutic range) in patients managed through the Coumadin Clinic Comply with nationally established INR goal guidelines Methods: Develop routine order sets Define team roles/expectations Develop point–of–care resource optimising access to INR testing. Educational program targeting stakeholders Monthly meeting auditing patients with goal analysis utilising tracking tools Review of process/outcome measures. Intervene for change utilising PDSA methodology PDSA Cycle 1: Retrospective data collection–2008 No systematic approach in place/data regarding patient TTR not available No structured staff/patient education program PDSA Cycle 2: Implement changes Web–based software purchased Structured approach to INR management implemented including stakeholder education program PDSA Cycle 3: Problem monitoring/notifying overdue INR patients Team member roles/responsibilities redefined 'Buddy system' implemented to monitor/notify overdue patients Results: TTR increased from 66%-2008 to 79%-2013 following implementation of structured policies/programs Re–implementation of education program, revision of policy/procedures TTR increased to 80% Jan–May–2015 Optimized point–of–care for INR testing–office finger–stick/remote laboratory testing/home monitoring Increased INR home monitoring Conclusion: With development of systematic approach to high risk patients on anticoagulation therapy, using a web–based software program, significant changes were evident: Improved patient follow–up, communication, decrease in overdue patient numbers Increased percentage of patients' within INR range Approach driven by the PDSA CQI methodology